Users satisfaction and perception on equipments and facilities of public playground at zone II, Selangor / Nor Hafiza Azmi - Azmi, Nor Hafiza (Faculty of Architecture, Planning and Surveying, 2013)
This report generally describes the research about the user satisfaction and perception on equipments and facilities of public playground. As knows, playground is a place where most of the children enjoy with it. Playground is an outdoor area set aside for recreation and play. Besides that, it also is a place where help to support development of children. Everything in the world has it own risk. It also includes the playground. The problem that usually faced by children is danger. It is cause by the poor condition of the playground equipments. The poor condition of equipments becomes worst from day to day because o f there are no specific responsible parties to do a maintenance work on it. The objective of this research is to identify the equipments and facilities o f public playground. Then, it is follow with the identification the user perception and satisfaction towards the equipments and facilities of public playground. Other objective is to make recommendation in improving the management of equipments and facilities of public playground. On this report it consists of introduction, literature review, research methodology, result and discussion and conclusion and recommendation. At the beginning, this report describe the introduction that covers the study background, problem statement, aims and objectives, scope and limitation, research methodology and significant of study. The main focus is aims and objective that has to plan carefully in order to achieve it at the result and finding.Then, it is discussed deeply at the literature review. It is discuss about the playground and all the equipments and facilities that installed it. It is to get more idea and understanding about the playground and easy to analysis the finding. The next is research methodology. At this section, it is discuss about the ways and strategy in order to get the information about the research. To get more understanding, the case study is including. From here, it can be seen clearly about the topic discussing. After all information got, the analysis and finding will be discuss. The results are show in graph to make it more understanding.